2015
DOI: 10.21891/jeseh.30143
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Teacher Beliefs through an Inquiry-Based Professional Development Program

Abstract: Inquiry-based instructional approaches are an effective means to actively engage students with science content and skills. This article examines the effects of an ongoing professional development program on middle and high school teachers' efficacy beliefs, confidence to teach research concepts and skills, and science content knowledge. Professional development activities included participation in a week long summer academy, designing and implementing inquirybased lessons within the classroom, examining and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Teachers’ knowledge, beliefs, and attitudes are key to the implementation of evidence-based practices (Fishman et al, 2003; McKeown et al, 2016; Sugai & Horner, 2020). General education elementary school teachers’ perceptions about interventions for students with ADHD are particularly important, given the majority of students with ADHD receive services within general education classrooms (Schnoes et al, 2006).…”
mentioning
confidence: 99%
“…Teachers’ knowledge, beliefs, and attitudes are key to the implementation of evidence-based practices (Fishman et al, 2003; McKeown et al, 2016; Sugai & Horner, 2020). General education elementary school teachers’ perceptions about interventions for students with ADHD are particularly important, given the majority of students with ADHD receive services within general education classrooms (Schnoes et al, 2006).…”
mentioning
confidence: 99%
“…Although the TEBS‐Self was developed in the United States, it had been translated and adapted for use in studies conducted in other contexts, such as China (Huangfu, ) and Iran (Babaei & Abednia, ; Tajeddin & Khodaverdi, ). The TEBS‐Self subscales demonstrated adequate reliability in previous research, with reliability estimates ranging from 0.66 to 0.99 (Khorshid, ; McKeown, Abrams, Slattum, & Kirk, ). Therefore, the measure was used in this study to assess preservice teachers’ self‐efficacy in classroom management.…”
Section: Methodsmentioning
confidence: 82%
“…The study's findings indicated that the collaborative inquiry process with enablers of time, flexibility and support from university faculty, increased educators' research acumen and student engagement in classrooms. It is believed that inquiry-based instructional approaches are an effective means to actively engage students with science content and skills (McKeown, et al, 2016). Their study examined the effect of ongoing professional development programs on middle and high school teachers' efficacy beliefs, confidence to teach research concepts and skills, and science content knowledge.…”
Section: Inquiry Based Methodsmentioning
confidence: 99%